Optimal cut-off values for obesity using classification tree in middle-aged adults living Rio de Janeiro city - Materko, Wollner; Santos, Edil Luis (International Journal of Research in Medical Sciences, 2017)
Background: The goal present study was to identify cut-off points for body mass index (BMI) and waist circumference (WC) to predict values of obesity based body fat percentage (BF%) using classification tree in middle-aged adults living Rio de Janeiro city, Brazil. Methods: The data was collected in a prospective cohort composed of 886 adults (443 men and 443 women) ranging from 30 to 59 years along two years (2010 - 2011) in Rio de Janeiro City, Brazil. All subjects were submitted to anthropometric evaluation and the gold standard was the percentage of body fat estimated by bioelectrical impedance analysis. The optimal sensitivity was achieved by adjusting BMI and WC cut-off values to predict obesity based on WHO criteria: BF% >25% in men and >35% in women according to the tree classification. Results: The best cut-off for BMI and WC were 28 kg/m2 and 99 cm, respectively, with a prediction of 99.4% overall tree sensitivity in men. For women, the best cut-off for BMI and WC were 26 kg/m2 and 90 cm, respectively, with a prediction of 90.1% overall tree sensitivity. Conclusions: The BMI and WC that corresponds to a BF% previously defining obesity is similar to other Western population, but different of the recommended by WHO and NCEP to BMI and WC thresholds, respectively, for defining obesity for both genders.